Business Retention and Expansion (BRE) Programs: Conducting Successful Business Retention and Expansion Visits - Henry M. Cothran (EDIS, 2006)
FE655, a 6-page fact sheet by Henry M. Cothran, describes the general guidelines for training Business Retention and Expansion teams to conduct successful business visits when the purpose of the visit is to conduct a formal survey. It is fifth in this series by the UF Department of Food and Resource Economics, published August 2006.